Preparation of nanoparticles of poorly water-soluble antioxidant curcumin by antisolvent precipitation methods - Kakran, Mitali (2013)
The objective of this study was to enhance the solubility and dissolution rate of a poorly water-soluble antioxidant, curcumin, by fabricating its nanoparticles with two methods: antisolvent precipitation with a syringe pump (APSP) and evaporative precipitation of nanosuspension (EPN). For APSP, process parameters like flow rate, stirring speed, solvent to antisolvent (SAS) ratio, and drug concentration were investigated to obtain the smallest particle size. For EPN, factors like drug concentration and the SAS ratio were examined. The effects of these process parameters on the supersaturation, nucleation, and growth rate were studied and optimized to obtain the smallest particle size of curcumin by both the methods. The average particle size of the original drug was about 10–12 μm and it was decreased to a mean diameter of 330 nm for the APSP method and to 150 nm for the EPN method. Overall, decreasing the drug concentration or increasing the flow rate, stirring rate, and antisolvent amount resulted in smaller particle sizes. Differential scanning calorimetry studies suggested lower crystallinity of curcumin particles fabricated. The solubility and dissolution rates of the prepared curcumin particles were significantly higher than those the original curcumin. The antioxidant activity, studied by the DPPH free radical-scavenging assay, was greater for the curcumin nanoparticles than the original curcumin. This study demonstrated that both the methods can successfully prepare curcumin into submicro to nanoparticles. However, drug particles prepared by EPN were smaller than those by APSP and hence, showed the slightly better solubility, dissolution rate, and antioxidant activity than the latter